Laminar shear stress-provoked cytoskeletal changes are mediated by epigenetic reprogramming of TIMP1 in human primary smooth muscle cells - da Silva, Rodrigo A. [UNESP]; Fernandes, Célio Jr da C. [UNESP]; Feltran, Geórgia da S. [UNESP]; Gomes, Anderson M. [UNESP]; de Camargo Andrade, Amanda Fantini [UNESP]; Andia, Denise C.; Peppelenbosch, Maikel P.; Zambuzzi, Willian F. [UNESP] (Wiley, 2019)
Whereas endothelial responses to shear stress are well-characterized, the cell physiological effects of shear stress in smooth muscle cells (SMCs) remain largely obscure. As SMCs are directly challenged by shear stress after endothelial denuding injury following procedures such as angioplasty or endarterectomy, characterization of these responses represents an important scientific question. Hence we decided to contrast cytoskeletal reorganization, epigenetic reprogramming, signaling transduction, and changes in miRNA (miRs) profiles in primary human aortic smooth muscle cells (AoSMCs) between unstressed cells and cells exposed to shear stress. We observed that shear stress-provoked reorganization of the actin cytoskeleton in an apparently Cofilin-dependent fashion and which related to altered integrin signaling, apparently caused by remodeling of the extracellular matrix. The latter appeared a downstream effect of increased expression of matrix metalloproteinases and downregulation of tissue metalloproteinase inhibitor 1 (TIMP1) protein levels. In turn, these effects related to shear stress-provoked changes in expression and nuclear localization of the epigenetic regulators demethylases TET1, TET2, DNMT1, DNMT3A and DNMT3B, HDAC6, and SIRT1. Accordingly, TIMP1 promotor CpG hypomethylation was a prominent effect, and resulted in a significant increase in TIMP1 transcription, which may also have related increased expression of miRs involved in modulating TIMP1 translation. Thus epigenetic-reprogramming of TIMP1 emerges as critical element in smooth muscle responses to mechanical signals and as epigenetic machinery is amendable to pharmacological manipulation, this pathway may have important clinical consequences.
Keywords: aortic smooth muscle cells; cytoskeleton; ECM; endothelium; epigenetic; TIMP